THE ESSENTIAL CONTRIBUTION OF CAPTIVE SUMATRAN ELEPHANT IN ELEPHANT TRAINING CENTER, WAY KAMBAS NATIONAL PARK FOR WILDLIFE GENETICS CONSERVATION - Rustiati, Elly Lestari; Priyambodo, Priyambodo; Yulianti, Yanti; Srihanto, Eko Agus; Pratiwi, Dian Neli; Virnarenata, Elsa; Novianasari, Tika; Krismuniarti, Elisabeth Devi; Saswiyanti, Enny (BIOVALENTIA: Biological Research Journal, 2020)
Way Kambas National Park (WKNP) is home of five protected big mammals including sumatran elephants.  It shares its border with 22 of 37 villages surrounding the national park.  Understanding their existence in the wild is a priority, and  wildlife genetics is a crucially needed. Besides poaching and habitat fragmentation, wildlife-human conflict is one big issue.  Elephant Training Center (ETC) in WKNP is built for semi in-situ conservation effort on captive sumatran elephants that mainly have conflict histories with local people.  Participative observation and bio-molecular analysis were conducted to learn the importance of captive Sumatran elephant for conservation effort.  Through captive sumatran elephants, database and applicable methods are expected to be developed supporting the conservation of their population in the wild.  Participative observation and molecular identification was carried on captive sumatran elephants in ETC, WKNP under multiple year Terapan grant of Ministry of Research and Technology Higher Education, Indonesia. Gene sequence and cytological analyses showed that the captive sumatran elephants are closely related and tend to be domesticated.  Translocation among ETC to avoid inbreeding, and maintaining the captive sumatran elephant as natural as possible are highly recommended. Developing genetic database can be a reference for both captive and wild sumatran elephants.